Reasons and Challenges of Former BSED English Students in Shifting to Other Program - Lanonte, Pearl Hanna; Hasim, Myra; Evedientes, Jundel; Gaan, Dayanara; Naparan, Genesis (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This qualitative study explores the reasons and challenges faced by former BSED English students who shifted to other programs. The study employed a case study approach, utilizing the Sharan Merriam technique and data triangulation method. Through Interviews with the seven former 1st-year BSED English students enrolled in the first semester, a thematic analysis was utilized to identify recurring patterns and themes. The study identifies reasons and challenges for students' shifting to other programs. The finding reveals that being inspired and influenced by others, as well as being curious about the program and the opportunity it offers, contribute to students’ reason to take up BSED English. Challenges encountered include difficulty with the topic and difficulty in speaking English. Students’ reasons for shifting are scholarship assistance and the difficulty of the major subject. The study concludes that these varying factors influenced the research participants to enroll in the BSED English program and shift to another program, indicating that it plays a significant role in students’ academic journey. This study gives insights into a crucial shift of students that has a significant implication for both students and the institution, as it holds an important role in students' career decision-making.